The Relationship Between Planning with the Success of the Planning Generation Forum Program in BKKBN West Sumatera Province - Nurhidayah, Nurhidayah; ‘Aini, Wirdatul (SAINTIS Publishing, 2019)
This study is motivated by the high rate of early marriage, drug abuse, and HIV/AIDS in West Sumatera in adolescents aged 10-24 years. This is allegedly due to the lack of attention of parents to adolescents of 12 years of compulsory education, parents' lack of attention to adolescence and lack of moral education to adolescents. This study aims to (1) Describe genre program planning, (2) Describe the success of genre programs, (3) relationship planning with success. This type of research is descriptive correlational with the population being PIK R adolescents in the GenRe program in the National Population and Family Planning Board (BKKBN) West Sumatera Province, amounting to 50 people. Samples were taken 10% of the population of 500 people. Sampling technique uses system random sampling. The data collection techniques are using questionnaires, and questionnaires as data collection tools. While the data analysis techniques in this study are using the percentage formula, and to see the relationship between them using Product Moment. The results of the study stated that (1) the implementation of the planning used by the ambassadors in the GenRe program in the West Sumatera provincial BKKBN was good enough, according to the teenagers' needs and strategies. (2) the success seen from the understanding, knowledge, and behavior of adolescent members of the PIK R on the GenRe program in the West Sumatra provincial BKKBN in daily life is quite good. (3) There is a significant relationship between the planning and success of the GenRe program in the BKKBN of West Sumatera province.